The synthesis and crystallographic characterization of 4-methylbenzenesulfonamide derivatives - Stenfors, Brock Anton; Ngassa, Felix Nyuangem (European Journal of Chemistry, 2021)
The sulfonamide moiety is present among a variety of biologically significant compounds. A facile synthesis is necessary to produce a variety of sulfonamides with the potential to improve human health. Herein, we report a facile methodology for the synthesis of 4-methylbenzenesulfonamides, amenable to a broad range of nitrogen nucleophiles. Implementing a semi-miscible biphasic solvent system resulted in higher yields, decreased reaction times, and a simplified workup over preliminary methods. Additionally, the crystal structures of five novel sulfonamide compounds and two polymorphs, have been determined by X-ray diffraction. Results obtained through spectroscopic characterization support the successful formation of the desired 4-methylbenzenesulfonamides.